Penerapan Sistem Informasi Akuntansi Penjualan Berbasis Web (Studi Kasus Pada Grand Yasmin Semarang) - Ari Siswati; Setya Indah Isnawati; Kasih Purwantini (Universitas Ngudi Waluyo, 2021)
Now there are many applications that use computer-based information systems. Therefore, the existence of computers is one of the means to be able to process data and information better. Grand Yasmin, as a trading business engaged in retail sales whose development still requires a strategic plan. Therefore, in this thesis the writer will create a web-based sales accounting application which is expected to be one of the solutions for the development of the company. The purpose of this research is to develop a sales accounting application system that has existed before, but is still very dependent on the presence of a courier / driver in inputting daily sales reports at each Grand Yasmin counter. The program to be developed is a sales accounting information system using a web application with a database as a storage medium, namely using MacromediaMX 2004 software and ASP as a programming language. The method used is qualitative data analysis. The result of this research is that the information obtained by head office employees is faster and makes their work easier without having to eliminate the role of office employees.Keywords:Techonology, system, sales report, software Macromedia MX 2004